2013
DOI: 10.1073/pnas.1301210110
|View full text |Cite
|
Sign up to set email alerts
|

Powering up with indirect reciprocity in a large-scale field experiment

Abstract: A defining aspect of human cooperation is the use of sophisticated indirect reciprocity. We observe others, talk about others, and act accordingly. We help those who help others, and we cooperate expecting that others will cooperate in return. Indirect reciprocity is based on reputation, which spreads by communication. A crucial aspect of indirect reciprocity is observability: reputation effects can support cooperation as long as peoples' actions can be observed by others. In evolutionary models of indirect re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
171
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 241 publications
(192 citation statements)
references
References 87 publications
6
171
1
5
Order By: Relevance
“…Several field studies have found evidence of humans exposing a pro-social behavior when being observed by others (recently confirmed in a field experiment with 2,000 individuals [19]) and also under the presence of subtle cues of being watched. Although there are also some studies that could not find such evidence.…”
Section: Introductionmentioning
confidence: 79%
“…Several field studies have found evidence of humans exposing a pro-social behavior when being observed by others (recently confirmed in a field experiment with 2,000 individuals [19]) and also under the presence of subtle cues of being watched. Although there are also some studies that could not find such evidence.…”
Section: Introductionmentioning
confidence: 79%
“…For example, a recent study has shown that reputation influenced the adoption of an energy program that actively reduced individuals' energy use during periods of high electricity demand, so to protect the entire system from blackouts. Individuals were more likely to adopt the program if their behavior could be observed by others (e.g., signing up with their names on sheets provided in communal spaces), and the effect was stronger for people living in apartment buildings, where interactions with their neighbors are more likely to occur compared to individual homes (Yoeli et al 2013). Also, people generally perceive the behavior of the majority as setting the norm for acceptable behavior.…”
Section: The Influence Of Social Contextmentioning
confidence: 99%
“…Evidence for the success of reputation-based incentives is not restricted to the lab. For example, a recent field experiment showed that a concern for good reputation can help in energy conservation, which is an important public good in the real world (Yoeli, Hoffman, Rand, and Nowak 2013).…”
Section: The Determinants Of Social Order Iii: Punishment and Other Imentioning
confidence: 99%